2013
DOI: 10.1186/cc13063
|View full text |Cite
|
Sign up to set email alerts
|

An automated and standardized neural index to quantify patient-ventilator interaction

Abstract: IntroductionThe aim of this study was to validate an automated, objective and standardized algorithm for quantifying and displaying patient-ventilator interaction.MethodsUsing a new method to detect patient-ventilator synchrony, the present study re-analyzed previously acquired and published data from 24 mechanically ventilated adult patients (Colombo et al., Crit Care Med. 2011 Nov;39(11):2452–7). Patient-ventilator interactions were evaluated by comparing ventilator pressure and diaphragm electrical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
107
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 15 publications
0
107
0
5
Order By: Relevance
“…This difficulty justifies attempts to develop automated systems [56,57] or to use an esophageal signal, such as the electrical activity of the diaphragm (EAdi) [58] or the Pes. The Pes recording can detect asynchrony by comparing the time occurrence of the changes in Pes with those of Paw and flow-time waveforms (Fig.…”
Section: Patient-ventilator Asynchrony and The Role Of Pes Monitoringmentioning
confidence: 99%
“…This difficulty justifies attempts to develop automated systems [56,57] or to use an esophageal signal, such as the electrical activity of the diaphragm (EAdi) [58] or the Pes. The Pes recording can detect asynchrony by comparing the time occurrence of the changes in Pes with those of Paw and flow-time waveforms (Fig.…”
Section: Patient-ventilator Asynchrony and The Role Of Pes Monitoringmentioning
confidence: 99%
“…Newer technological developments and research have demonstrated the ability to effectively detect asynchronies and dysnchronies. 4,11 This type of technology may take time to permeate to routine patient care but, given its relevance, should top the list of developments. We take this moment to caution that technology does not replace education; one without the other makes us dangerous, but both together make us more effective.…”
Section: See the Original Study On Page 144mentioning
confidence: 99%
“…Reviews, trials, and reports use different definitions for asynchrony and its types. [2][3][4][5] This leads to confusion and hinders our ability to determine the incidence and impact of patient-ventilator interactions, their association with each mode of ventilation, and patient outcomes. One such example is the definition of double-triggering.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tested on a small sample of patients, the accuracy of the computerized automatic ineffective inspiratory efforts algorithm during expiration was similar to that when compared to expert critical care staff and the electrical activity of the diaphragm. Sinderby et al 50 tested a new method of automatically detecting, quantifying, and displaying patient-ventilator interaction based on the measurements of electrical activity of the diaphragm and airway pressure waveforms. This method provides clinicians with a dashboard style of graphical display that allows a rapid overview of patient-ventilator interaction and breathing pattern.…”
Section: Information Technologiesmentioning
confidence: 99%